Comparative Analysis of Consumer Experience Against Business Strategy in E-Commerce: Case Study of Shopee and Tokopedia - Hakim, Lukman; Karima, Inna Sabily; Oktavian, Rahmat; Muarif, Muhammad Riski; Hidayat, Ahmad (Journal Collabits, 2024)
The purpose of this research is to compare customer experiences in e-commerce. Electronic commerce is a global phenomenon that has changed the way businesses interact with consumers. It involves buying, selling and exchanging goods and services through online platforms. E-commerce has grown rapidly along with advances in information technology in business strategies. However, the challenges faced in e-commerce include the security of online transactions, intense competition, and the need to build customer trust. Examples of e- commerce are SHOPEE, LAZADA, TOKOPEDIA and others. It's just that in this research theresearcher will compare the 3 studies in terms of customer experience. SHOPEE, LAZADA AND TOKOPEDIA are three e-commerce platforms operating in Southeast Asia, including Indonesia. By using quantitative methods.